2015
DOI: 10.1111/jfpe.12273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Controlled Freezing‐Point Vacuum Drying on Color and Flavor of Muraenesox cinereus Fillets

Abstract: In this study, the method of maintaining the controlled freezing point and the effect of controlled freezing‐point vacuum drying (CFVD) on the quality of Muraenesox cinereus fillets were investigated. The quality assessment was based on color, 5‐inosine monophosphate (IMP), free amino acids (FAAs) and volatile compounds. Furthermore, comparisons were made among CFVD samples, those dried by hot air drying (HAD) and vacuum freeze drying (VFD). The results showed that the fillet temperature can be controlled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…They are commonly processed in large quantities into refrigerated, roasted, pickled, or semi-dried muscle products before being transported, exported, and consumed. Previous studies on the abundant nutritional compounds in fresh eel muscle, the drying process and its kinetics, quality changes during different drying processes, and roast cooking process have been conducted ( Li et al, 2017 , Bi et al, 2018 ). However, according to the literatures, no detailed investigations on the protein denaturation and the alterations of pike eel muscle tissues under cold stress or other conditions have been conducted in depth.…”
Section: Introductionmentioning
confidence: 99%
“…They are commonly processed in large quantities into refrigerated, roasted, pickled, or semi-dried muscle products before being transported, exported, and consumed. Previous studies on the abundant nutritional compounds in fresh eel muscle, the drying process and its kinetics, quality changes during different drying processes, and roast cooking process have been conducted ( Li et al, 2017 , Bi et al, 2018 ). However, according to the literatures, no detailed investigations on the protein denaturation and the alterations of pike eel muscle tissues under cold stress or other conditions have been conducted in depth.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of FAAs was analyzed by an automatic amino acid analyzer (L‐8800, Hitachi) based on previously reported method with slight modifications (Jia et al., 2017). Samples (2 g) were homogenized with 15 ml of 15% TCA and stood for 2 hr, then centrifuged at 10,000 rpm at 4°C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies showed that the contents of aldehydes, ketones, and alcohols were lower in VFDS and cold-air-dried fillets, while the levels of aldehydes, ketones, and alcohols were higher in HADS and VDS fillets. The reason may be that the levels of these compounds were inhibited in the low-temperature drying process [ 2 , 3 ]. Meanwhile, some of the literature reported that the high temperature often promoted the formation of other volatile flavor compounds.…”
Section: Introductionmentioning
confidence: 99%